Dynamics of Crank-Piston Mechanisms - Davitashvili, Nodar; Bakhshaliev, Valeh (Springer Nature Singapore : Imprint: Springer, 2016)
This monograph focuses on the dynamical research work on crank-piston mechanisms considering basic and additional motions. In order to have full dynamical analyses of piston machines and their mechanisms, the book studies the crank-piston mechanisms with clearances in kinematic pairs. The tasks are carried out by focusing on friction, wear and impacts in mechanisms, as well as cracks formation in links and elasticity of details, with distributed and concentrated masses. Then, the reliability and durability of the mechanisms of piston machines is applied on oil and gas transportation. The monograph is meant for design specialists. It is also useful for specialists-manufacturers and designers of piston machines, scientists and lecturers, doctoral students.